Quality Services Moderation on Moral Impact of Taxpayers and Tax Penalties on Compliance Taxpayers - Ridhan Rahmah (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study examines the effect of taxpayer morale and tax sanctions on taxpayer compliance with service quality as a moderating variable. This study uses a survey method by distributing questionnaires directly and via google form to individual taxpayers registered at KPP Pratama North Makassar. A simple random sampling method was used to draw samples in this study. Samples that can be processed are 280 individual taxpayers. Data analysis using Partial Least Square (PLS) through SmartPLS 2 software. The results of this study indicate that taxpayer morale has a positive effect on taxpayer compliance. Tax sanctions have a positive effect on taxpayer compliance. In addition, service quality does not moderate the effect of taxpayer morale on taxpayer compliance. Service quality weakens the effect of tax sanctions on taxpayer compliance.